Lung Perfusion Scan for Pulmonary Embolism and Shunt Detection: An Effective Diagnostic Tool - Sana Munir Gill; Areej Ijaz; Aamna Hassan (Journal of the Pakistan Medical Association, 2025)
Pulmonary embolism (PE) can lead to chronic thromboembolic pulmonary hypertension (CTEPH) which can result in right heart failure. Therefore, timely management of this condition can save patients from serious complications. In the department of Nuclear Medicine, ventilation perfusion (V/Q) scan has been used to supplement detection of PE especially in cases where contrast based computed tomography pulmonary angiography (CTPA) cannot be performed. With the advent of single photon emission computed tomography (SPECT/CT), perfusion scan with SPECT/CT is being frequently used. It has also been used for the diagnosis of various other indications such as right to left cardiac shunts in addition to PE. Technetium 99m macroaggregated human serum albumin (99mTc HSA) is commonly used in lung perfusion scans. It can also be taken up by extra pulmonary organs such as brain or kidneys due to presence of shunt. We present an interesting case of simultaneous detection of PE and right to left shunt in a young patient. Keywords: Pulmonary embolism, ventilation perfusion scan, right to left shunt, brain uptake.